Profissionalidade e profissionalização na coordenação pedagógica escolar: uma revisão sistemática de teses e dissertações - Ricardo, Vanessa Vial (2022)
The experience as a school pedagogical coordinator raised some concerns about this role, her training, her specificity as a profession and the professional identity of this role. Faced with such questions, the objective of this research was to identify and understand the main elements that constitute the concepts and processes of professionalism and professionalization of school pedagogical coordinators. With this objective established, we opted for the perspective of a qualitative approach to research, and, with a systematic review methodological path, which makes it possible to investigate these concepts and their elements, and the constitution processes, in the research already carried out, discussed and revealed in a given time cut, due to the increase in academic productions on pedagogical coordination, this cut was established from the 2000s 2018 onwards. From the proposed focus, the methodological actions unfolded in the data collection in the Theses and Dissertations Catalog - CAPES, which had 23 researches selected to compose analytical corpus. The chapters present a historical outline of the function and attributions of the pedagogical coordination and the legal historicity of the function, in addition to highlighting the theoretical foundation for the study and deepening of the terms were about professionality (DUBAR, 2005; DAVIS E GORZONI, 2017; AMBROSETTI E ALMEIDA, 2009; ANDRÉ E PLACCO 2007; SACRISTÁN, 1995; ROLDÃO 2008; NÓVOA, 2017) and for professionalization (TARDIF 2013; LENGERT 2011; NÓVOA2017). After collecting data in academic productions, the systematic review of research was inspired by Romanowski (2006). As for the concept of terms; professionalism is understood as a set of attributions of the subject and his profession and as for professionalization as a collective movement of validation and legitimation of training, doing and specific knowledge. The main results of the elements indicate that the process of constitution of professionalism and professionalization of the school pedagogical coordinator are intertwined, however they have their own characteristics, therefore, professionalism involves two main elements organized into two categories; one of self-knowledge (from the coordinators for themselves) and the other of recognition of their formative role (from the coordinators to the other). And the main elements of professionalization involve working conditions and specific continuing education in which professional autonomy is provided and the community is strengthened.